2018
DOI: 10.1007/s10646-018-1928-2
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis and paradoxical effects of pea (Pisum sativum L.) parameters upon exposure to formaldehyde in a wide range of doses

Abstract: Formaldehyde is a widespread pollutant of soil near roads including agricultural lands. Non-monotonic changes (hormesis and paradoxical effects) in chlorophyll (Ch) and carotenoid (Car) contents, the lipid peroxidation (LP) rate in plant leaves and growth parameters (GP) of plants can be caused by various pollutants. Hormesis is a biphasic dose-response phenomenon, characterised by low-dose stimulation and high-dose inhibition. The remaining types of non-monotonic responses are classified as paradoxical effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…These ndings are in alignment with the ndings of Khan et al (2023) Formaldehyde application also signi cantly escalated the chlorophyll and carotenoid content in this study. This follows the pattern of previous studies conducted on Pisum sativum and C. comosum against formaldehyde stress (Erofeeva, 2018;Paresh et al 2018;Khan et al 2023). Under paradoxical effects, the toxic impact of higher formaldehyde level is reduced, leading to increased chlorophyll content in plants (Erofeeva, 2018).…”
supporting
confidence: 88%
“…These ndings are in alignment with the ndings of Khan et al (2023) Formaldehyde application also signi cantly escalated the chlorophyll and carotenoid content in this study. This follows the pattern of previous studies conducted on Pisum sativum and C. comosum against formaldehyde stress (Erofeeva, 2018;Paresh et al 2018;Khan et al 2023). Under paradoxical effects, the toxic impact of higher formaldehyde level is reduced, leading to increased chlorophyll content in plants (Erofeeva, 2018).…”
supporting
confidence: 88%
“…Biological systems exhibit a variety of unexpected, sometimes paradoxical, behaviour. Examples include catastrophic shifts [1] at tipping points in ecosystems [2], phase changes in polyphenic insects [3] and hormesis in toxicology, whereby a cell or organism exhibits a biphasic response when exposed to increasing amounts of a substance or external conditions [4][5][6]. Ecological paradoxes involving interactions between two or more species include coexistence of competing species [7] and the 'paradox of the plankton' [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency of non-monotonic dose-effect relationships was revealed for various plant indices under stressful environments [37][38][39], including the effects of chemical pollutants on physiological and biochemical parameters [43,44,57], as well as on leaf FA [44,58]. In this study, we first found non-monotonic responses in development of leaf bilateral asymmetry type, that is, for leaf morphogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…However, it is known that non-monotonic dose-response relations (with maximums and/or minimums) which include hormesis [37][38][39] and paradoxical effects [40,41] are frequently found for different plant species and parameters, including various pollutant exposures [42][43][44][45][46][47]. Hence, an increase in the pollution level will not always be accompanied by plant index deteriorations.…”
Section: Introductionmentioning
confidence: 99%